The Catholic Church as a secularization factor amongst Jaen peasants migrating from the Andes - Lecaros, Véronique (2021)
This article presents the way religious catholic people get involved in the protection of the ecosystem of the Jaen Vicariate, entrusted to the Company of Jesus. Peasants of the zone, who are migrants from the mountains regions, exploit their new habitat according to their ancestors’ traditions shaped in different context. These agricultural methods are inserted in an enchanted worldview. Religious people to encouragepractices respectful of the environment fight against harmful beliefs and promote a rational and scientific comprehension of the situation, a secularized one. Nonetheless, their initiative is not fully successful. It is very difficult to deal with one aspect of a worldview and change it. Besides, peasants, who often experience great necessities, have assimilated the logic and the expectations of the consumer society. Good techniquesare not enough; as pope Frances states, a good equilibrium between human beings and between human beings and nature is necessary. These reflections are part of the international debate on the good management of the Amazonian region and its protection.